2023
DOI: 10.3390/nu15214613
|View full text |Cite
|
Sign up to set email alerts
|

The Global Burden of Type 2 Diabetes Attributable to Dietary Risks: Insights from the Global Burden of Disease Study 2019

Alina Ioana Forray,
Mădălina Adina Coman,
Ruxandra Simonescu-Colan
et al.

Abstract: The Global Burden of Disease Study (GBD) 2019 reveals an increasing prevalence of Type 2 Diabetes Mellitus (T2DM) from 1990 to 2019. This study delves into the role of dietary risk factors across different demographic and socioeconomic groups. Utilizing data from the GBD 2019, it analyzes age-adjusted T2DM metrics—death counts, Disability-Adjusted Life Years (DALYs), and Age-Standardized Rates (ASRs)—stratified by age, sex, and region. The study employed Estimated Annual Percentage Changes (EAPCs) to track tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Within the Global Burden of Disease Study (GBD), PM2.5 was identified as the third major contributory factor for type 2 diabetes (Collaborators, 2020). GBD 2019 findings suggested that approximately 20% of the global burden related to type 2 diabetes may be attributed to PM2.5 exposure (Collaborators, 2020;Forray et al, 2023). PM2.5 is made up of several components, such as black carbon (BC), chloride (Cl), nitrate (NO3 -), ammonium (NH4 + ), sulfate radical (SO4 2-), and organic matter (OM) (Wei et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Within the Global Burden of Disease Study (GBD), PM2.5 was identified as the third major contributory factor for type 2 diabetes (Collaborators, 2020). GBD 2019 findings suggested that approximately 20% of the global burden related to type 2 diabetes may be attributed to PM2.5 exposure (Collaborators, 2020;Forray et al, 2023). PM2.5 is made up of several components, such as black carbon (BC), chloride (Cl), nitrate (NO3 -), ammonium (NH4 + ), sulfate radical (SO4 2-), and organic matter (OM) (Wei et al, 2023).…”
Section: Introductionmentioning
confidence: 99%